Study of Cu Recovery Comparison of Fresh, Stockpiled, and Mixed Ores Processing in Batu Hijau Mine – Sumbawa Island, Indonesia - Surya Hadi; Agung Damar Syakti; Didik Supriadi Agustawijaya; Wahyu Dian Silviani; Karel Pramono; Rissa Anungstri; Jorina Waworuntu (The Journal of Pure and Applied Chemistry Research, 2022)
Batu Hijau mine is one of the mining areas in Indonesia that have been operated for 20 years. The main concentrate product in Batu Hijau contains the primary minerals copper (Cu) and gold (Au). However, the mine is not only processing the fresh mined ore but also store the low-grade ore in the stockpile. Therefore, this study compares the Cu recovery in different ore stockpile processing on and changes in the concentration of dissolved Cu in the tailings that potentially contaminated the environment. Chemical analysis of solid and dissolved Cu uses standard methods by strictly carrying out quality assurance and quality control (QA/QC) procedures to ensure the resulting data has high validity. The results showed that there is a slight increase in Cu’s solubility in liquid fraction of tailings and the recovery decrease when ores were processed from stockpiles. However, the recovery reduction is anticipated by flotation with controlled potential sulphidisation (CPS) using sodium hydrosulphide (NaHS). Besides, the CPS also ensure that only small amount of dissolved Cu that dumped in the tailings. Hence, the dissolved Cu concentration can be monitories to reduce the possible impact on the environment.